The t(8;9)(p22;p24) is a recurrent abnormality in chronic and acute leukemia that fuses PCM1 to JAK2 - Reiter, Andreas; Walz, Christoph; Watmore, Ann; Schoch, Claudia; Blau, Ilona; Schlegelberger, Brigitte; Berger, Ute; Telford, Nick; Aruliah, Shilani; Yin, John A.; Vanstraelen, Danny; Barker, Helen F.; et al. (Cancer research, 2005)
We have identified a t(8;9)(p21-23;p23-24) in seven male patients (mean age 50, range 32-74) with diverse hematologic malignancies and clinical outcomes: atypical chronic myeloid leukemia/chronic eosinophilic leukemia (n = 5), secondary acute myeloid leukemia (n = 1), and pre-B-cell acute lymphoblastic leukemia (n = 1). Initial fluorescence in situ hybridization studies of one patient indicated that the nonreceptor tyrosine kinase Janus-activated kinase 2 (JAK2) at 9p24 was disrupted. Rapid amplification of cDNA ends-PCR identified the 8p22 partner gene as human autoantigen pericentriolar material (PCM1), a gene encoding a large centrosomal protein with multiple coiled-coil domains. Reverse transcription-PCR and fluorescence in situ hybridization confirmed the fusion in this case and also identified PCM1-JAK2 in the six other t(8;9) patients. The breakpoints were variable in both genes, but in all cases the chimeric mRNA is predicted to encode a protein that retains several of the predicted coiled-coil domains from PCM1 and the entire tyrosine kinase domain of JAK2. Reciprocal JAK2-PCM1 mRNA was not detected in any patient. We conclude that human autoantigen pericentriolar material (PCM1)-JAK2 is a novel, recurrent fusion gene in hematologic malignancies. Patients with PCM1-JAK2 disease are attractive candidates for targeted signal transduction therapy.
Gesehen am 11.05.2022